Heterogeneity of Catalase in Maturing and Germinated Cotton Seeds - Kunce, Christine M. (1986)
To investigate possible charge and size heterogeneity of catalase (EC 1.11.1.6) in cotton (Gossypium hirsutum L. cv Deltapine 62), extracts of cotyledons from different developmental ages were subjected to nondenaturing polyacrylamide gel electrophoresis and isoelectric focusing. Special precautions (e.g. fresh homogenates, reducing media) were necessary to prevent artefacts due to enzyme modification during extraction and storage. When the gels were stained for enzyme activity, two distinct electrophoretic forms of catalase were resolved in extracts of maturing and mature cotton seeds. In germinated seeds, three additional cathodic forms were detected revealing a total of five electrophoretic variants. In green cotyledons, the two anodic forms characteristic of ungerminated seeds were less active; whereas, the most cathodic form was predominant. All forms of catalase were found in isolated glyoxysomes. Corresponding electrophoretic patterns were found on Western blots probed with anticatalase serum; no immunoreactive, catalytically inactive forms were detected. Western blots of sodium dodecyl sulfate-polyacrylamide gels revealed only one immunoreactive (55 kilodaltons) polypeptide in cotton extracts of all developmental ages. Results from isoelectric focusing and Ferguson plots indicate that the electrophoretic variants of catalase are charge isomers with a molecular weight of approximately 230,000.